Climate change and adventure guiding: The role of nature connection in guide wellbeing - Valdivielso Martínez, Elsa; Houge Mackenzie, Susan (Frontiers in Public Health, 2022)
Ecological challenges are quickly shaping the future of the tourism industry with an increasing focus on how to develop more sustainable adventure tourism practices. Adventure guides play an important role in this transition and in shaping client experiences, however there is a need to better understand how climate change may have important impacts on guides’ wellbeing. This study explored adventure guides’ experiences of nature connectedness and potential links between climate change, nature connection, and wellbeing for adventure guides. Semi-structured qualitative interviews (x= 11) with adventure guides were analysed using reflexive thematic analysis to explore these relationships. Adventure guides reported experiencing meaningful connections and relationships with the natural environments in which they worked, while also highlighting why not all types of nature nor time spent outdoors facilitated this connection. Guides that reported being more connected to nature also reported a higher sense of environmental responsibility, and guides described how this often created ‘ethical dilemmas’ in seeking to resolve tensions between their deep connection to nature and unsustainable practices that their guiding work often entailed. Analysis also highlighted the value and wellbeing guides derived from sharing their love of nature with clients. These findings expand emerging theoretical models of adventure guide wellbeing, and suggest a range of practices that can support a more ecologically sustainable adventure tourism industry.